0044 Association Between Chronotype and Circulating Levels of Interleukin-6 in Colorectal Cancer Patients: Preliminary Results from the ColoCare Study. (27th May 2020) - Peoples, A R; Gigic, B; Ose, J; Himbert, C; Hardikar, S; Boehm, J; Schrotz-King, P; Ulrich, A B; Schneider, M; Li, C I; Shibata, D; Siegel, E M; et al.
Abstract: Introduction: Accumulating evidence suggests that chronotype, i.e., circadian topology of an individual indicating morning or evening type, is associated with inflammation. To date, no study has examined the relationship between chronotype and inflammation in colorectal cancer patients. We investigated the associations between chronotype and inflammatory and angiogenesis biomarkers in colorectal cancer patients. Methods: We used pre-surgery serum samples from n=67 newly diagnosed colorectal cancer patients (stage I-IV) recruited at the ColoCare Study site in Heidelberg, Germany. The ColoCare Study is an ongoing, international, multisite, prospective cohort study in colorectal cancer patients. Inflammatory and angiogenesis biomarkers [c-reactive protein (CRP), interleukin (IL)‐6, IL‐8, monocyte chemoattractant protein-1 (MCP-1), soluble intercellular adhesion molecule-1 (sICAM-1), soluble vascular cell adhesion molecule-1 (sVCAM-1)] were measured at the Huntsman Cancer Institute, USA using the Meso Scale Discovery platform and were log transformed. Chronotype was assessed prior to surgery with the reduced Morningness-Eveningness Questionnaire (rMEQ; scale 4–25; a higher score indicates more morning-type). Patients were dichotomized, based on the median values for rMEQ, into 2 groups: rMEQ-low (score≤16.0; n=35; indicating more evening-type) or rMEQ-high (score>16.0; n=32; indicating more morning-type). Results: Using Mann-Whitney U test, we observed that rMEQ-low group (i.e., more evening-type) compared to rMEQ-high group (i.e., more morning-type) had approx. two times significantly higher levels of log transformed IL-6 (mean=2.24 vs. 1.30; U=382.0; Z=-2.23; p=0.03), but not for other inflammatory or angiogenesis biomarkers. This association between chronotype and IL-6 was maintained even after adjusting for age, sex, tumor stage, tumor site, and sleep duration using a generalized estimating equations model (adjusted mean difference=1.10; 95% confidence interval=0.33, 1.88; p=0.01; effect size, Cohen's d=0.69). Conclusion: These preliminary findings suggest that the evening chronotype is associated with increased IL-6 inflammatory biomarker in colorectal cancer patients. Further research is needed to confirm and understand the mechanistic underpinnings of the observed results. Support: Funding: NCI U01 CA206110, R01 CA189184, and R01 CA207371.